Selective sequencing on an industrial scale - Munro, Rory J. (2025)
The production of real-time sequence data from native, long single-molecule Deoxyribonucleic acid and Ribonucleic acid is unique to Oxford Nanopore Technologies sequencers. Real-time analysis can guide the application of both run-until and read-until, which increases the efficiency of sequencing runs. Run-until allows users to stop a sequencing run at certain thresholds, preserving flow cell health. Read-until, or adaptive-sampling, can focus genome-wide sequencing onto specific regions of interest enriching coverage over these targets. In Chapter 1, we discuss the development and application of our fully-customisable nanopore simulator, which allowed us to test these tools whilst avoiding the costs of performing real sequencing.